The rumanian delegation at the WFTU congress: standing: Mustetiu and 3 interpretators, sitting: Bratfaleano, Sencovici, Levin, Serban, Apostol, Nuselevici-Moldovanu (1945)
The rumanian delegation at the WFTU congress: standing: Mustetiu and 3 interpretators, sitting: Bratfaleano, Sencovici, Levin, Serban, Apostol, Nuselevici-Moldovanu.